Risk Factors of Catheter-Related Infection in Patients Undergoing Hemodialysis Using Double Lumen Catheter at Dr. M. Djamil Hospital Padang - Muhammad Iqbal; Raflis Rustam; Vendry Rivaldy (HM Publisher, 2022)
Background. Chronic kidney disease (CKD) is a terminal disease requiring hemodialysis. Hemodialysis requires vascular access using a double lumen catheter (DLC). However, the use of DLC may increase complications mainly infection, either infection of exit site or bloodstream. This study is aimed to seek risk factors contributing to the incidence of central catheter-related infections in CKD patients with DLC undergoing HD at Dr. M. Djamil Hospital, Padang. Methods. This study is a prospective study on patients undergoing HD at Dr. M. Djamil Hospital, Padang. This study using consecutive sampling technique. Data were analyzed using SPSS version 25.0. Results. This study involved 40 CKD patients undergoing HD. Majority of the samples had bloodstream infections (67.5%). Clinical manifestations of purulent secretion, duration of catheter used, and hypoalbuminemia had significant differences in the incidence of DLC infection based on bloodstream infection and exit site infection (p<0.05). The most common bacterial found was Pseudomonas aeruginosa (22.5%) which was sensitive to ceftazidime, cefepime, meropenem, amikacin, gentamicin, ciprofloxacin. Conclusion. Factors contributing to the incidence of DLC-related infections at Dr. M. Djamil Hospital are duration of catheter use and hypoalbuminemia. Pseudomonas aeruginosa is the most common cause of DLC-related infections.